Preventing Re-Emergence of COVID-19: A National Survey of Public Risk Perceptions and Behavioural Intentions Concerning Travel Plan Among Taiwanese - Li Ping Wong; Li Ping Wong; Ching-Ju Chiu; Haridah Alias; Tony Szu-Hsien Lee; Zhijian Hu; Yulan Lin (Frontiers in Public Health, 2021)
Background: The objectives of this study were to investigate risk perceptions and travel intention among the general public in Taiwan during the COVID-19 outbreak.Methods: This study used a cross-sectional online survey to collect data. The questionnaire was disseminated via the social media platform (LINE and Facebook) to the general public.Results: A total of 3,237 complete responses were received, of whom 5.8% (95% CI 5.1–6.7) of the participants reported intent to travel to overseas countries with an apparent community spread and 5.5% (95% CI 4.7–6.3) reported intent to travel to other overseas countries in the next 1 month. A relatively higher proportion (46.5%; 95% CI 44.7–48.2) reported intention for domestic travelling. Participants who viewed travelling to only be risky for older adults or those with medical conditions (OR = 2.19; 95% CI 1.38–3.47) and who perceived that one will not get infected if one takes recommended precautionary measures (OR = 3.12; 95% CI 1.85–5.27) reported higher travelling intention to overseas countries with an apparent community spread.Conclusions: Overall, the findings suggest that risk perceptions were depicted as a strong influence of travel intentions.